2009
DOI: 10.1111/j.1474-9726.2008.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐cell diversity decreases in old age and is correlated with poor health status

Abstract: SummaryOlder people suffer from a decline in immune system, which affects their ability to respond to infections and to raise efficient responses to vaccines. Effective and specific antibodies in responses from older individuals are decreased in favour of non-specific antibody production. We investigated the B-cell repertoire in DNA samples from peripheral blood of individuals aged 86-94 years, and a control group aged 19 -54 years, using spectratype analysis of the IGHV complementarity determining region (CDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
275
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 383 publications
(292 citation statements)
references
References 35 publications
14
275
2
1
Order By: Relevance
“…S3B). repertoire structure not found in young subjects, where one or several B-cell lineages are expanded to abnormal proportions (8,23). This finding is confirmed by our data (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…S3B). repertoire structure not found in young subjects, where one or several B-cell lineages are expanded to abnormal proportions (8,23). This finding is confirmed by our data (Fig.…”
Section: Resultssupporting
confidence: 91%
“…IGH repertoire diversity, corrected for uncaptured sequences using the Chao1 estimator (21), was seen to decrease with age (Fig. 3A), consistent with previous studies (8,23). A recently proposed estimator for the unseen fraction of sequences (33) gave similar results (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Indeed, an increased oligoclonality and a reduced frequency of somatic hypermutation in the elderly response to pneumococcal vaccination has been reported (Kolibab et al 2005). The consequence is a collapse in B cell diversity in elderly people which is correlated with poor health status in these subjects (Gibson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have, for example: revealed the association of certain germline genotypes with susceptibility to such diseases as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and multiple sclerosis (MS) (5,6); found correlations of age with a reduced Ig clonal diversity and less intense response to immune challenge (7,8); found overly expanded clones in cases of lymphoma (9,10); and discovered convergent Ig evolution across subjects in response to certain immune challenges (11,12). These repertoire-sequencing (Rep-Seq) studies have benefitted from improvements in sequencing technologies, which allow for the generation of millions of reads per run (13).…”
mentioning
confidence: 99%